1998
DOI: 10.1126/science.280.5360.95
|View full text |Cite
|
Sign up to set email alerts
|

Strong Regularities in World Wide Web Surfing

Abstract: One of the most common modes of accessing information in the World Wide Web is surfing from one document to another along hyperlinks. Several large empirical studies have revealed common patterns of surfing behavior. A model that assumes that users make a sequence of decisions to proceed to another page, continuing as long as the value of the current page exceeds some threshold, yields the probability distribution for the number of pages that a user visits within a given Web site. This model was verified by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
388
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(404 citation statements)
references
References 13 publications
14
388
1
1
Order By: Relevance
“…For instance, the hierarchically connected networks are shown [10] to be robust to large failure rates, however, they are vulnerable to removal of a few 'key nodes'. The inhomogeneous structure of connections has been found in metabolic cycles [1], in various social networks [2], including the science citation network [3], and the Internet [4] and the world-wide Web [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the hierarchically connected networks are shown [10] to be robust to large failure rates, however, they are vulnerable to removal of a few 'key nodes'. The inhomogeneous structure of connections has been found in metabolic cycles [1], in various social networks [2], including the science citation network [3], and the Internet [4] and the world-wide Web [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the evolution of complex networks [1][2][3][4][5][6][7][8][9][10][11][12][13] remains a challenging problem of modern statistical physics. Modeling the dynamic structure of these networks has significant practical applications, for instance in the design of search and control algorithms and in predicting emergence of new phenomena in information networks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that users demonstrated regularities in their surfing patterns [12]. Our characterization results presented in this paper also indicate that users have highly repetitive network-connection patterns.…”
mentioning
confidence: 48%
“…This is stronger than our linkage conjecture, since it implies a positive correlation between V L and V L−1 (analogous to our relevance autocorrelation) for any µ > 0. Huberman et al (1998) find that the distribution of surfing depth (clicks per Web site) derived from the above random walk equation is a very good predictive model of human browsing behavior. Although our conjecture on the value of linkage topology is more modest, it finds strong support in these findings.…”
Section: Other Related Projectsmentioning
confidence: 99%